Book Review: Michael Baun and Dan Marek (eds.) The New Member States and the European Union. Foreign Policy and Europeanization - Adelin Dumitru (Romanian Journal of European Affairs)
A radical decision at the time, the 2004 enlargement constituted a critical juncture for the Central and Eastern European Countries. Although a great deal of literature has been written in regard to other aspects of Europeanization, the effects of EU membership on the foreign policy of the new member states have been rarely discussed. This is what the volume coordinated by Michael Baun and Dan Marek seeks to accomplish, namely to fill a gap in the European Studies with a series of articles explaining the more or less significant institutional and behavioural changes which occurred at the level of the new member states’ political elites. Focusing on three main domains in which Europeanization purportedly occurred, namely national preferences and interests, institutions and procedures, foreign policy strategies and actions, the studies gathered in this volume provide a useful overview of the effects of EU membership on what was traditionally known as “foreign policy”.